Right-to-work law: boicote institucionalizado? - Espósito, Katiuscia Moreno Galhera (Revista Videre, 2014)
Fazil MIHLAR (ed.): Unions and right-to-work Laws: the global evidence of their impact on employment. Toronto, The Fraser Institute, 1997. 230 páginas. ISBN 0-88975-179-X